A possible subthreshold pole in S 11 channel from πN Roy-Steiner equation analyses - Xiong-Hui Cao; Qu-Zhi Li; Han-Qing Zheng (Journal of High Energy Physics, 2022)
Abstract The hyperbolic version of Roy-Steiner equation describing low energy πN scatterings, with larger analyticity domain in the complex s plane is solved. The numerical results on phase shifts of low partial waves are in agreement with that of Hoferichter et al. [Phys. Rept. 625 (2016) 1]. A subthreshold pole in S 11 channel is found located at s $$ \sqrt{s} $$ = (918 ± 3) − i(163 ± 9) MeV.